PERANCANGAN SPIRITUAL CENTER DENGAN PENDEKATAN ARSITEKTUR SYMBOLIC DI KOTA TOMOHON - Heryan Balo; Claudia I Lombok; Cindy M. Liando (Program Studi Arsitektur Fakultas Teknik Universitas Negeri Manado, 2023)
pirituality is the highest human divine consciousness since ancient times, then developed in such a way until now. Since ancient times, architecture has been a physical component as a means for humans to express their spirituality. These traditions and practices are full of symbolism and meaning which are expressed in the development of awareness and enlightenment. The distribution of the population and the dynamics of the cultural life of mankind shape each of the different spiritual traditions. These differences form a rich and authentic diversity. To achieve harmony of civilization, of course, architecture is one of the most beautiful components in realizing expressions that can trigger this divine awareness. Indonesia is a country rich in natural beauty, tribes and traditions, awareness is needed to preserve this, especially in the northern hemisphere, namely the cities of Manado and Tomohon. Social harmony in the area requires an important appreciation through the provision of spiritual facilities that cover universally. The idea of this architectural design is an illustration of ideas and a contribution of ideas for the existence of a spiritual facility that elevates the authentic meaning and symbolism of each religious tradition in Indonesia.